(untitled) (Future Cities and Environment, 2025)
Smart cities around the world promise its citizens more resilient, inclusive and sustainable living environment. They present an integration of physical and digital planning and are perceived by governments around the world as a path to achieve a new urban Utopia. However, its application in developing countries is full of challenges, the question is how inclusive new smart cities will be in countries facing high percentage of poverty and illiteracy and how they can contribute in sustainable urban development to these countries. In Egypt, a New Administrative Capital is currently under construction. The new smart city promises a high-quality living for Egyptians. However, there is a debate about how inclusive it will be and how the smart city model can be adopted in Egypt. The paper presents a critical reflection on the topic. We question this utopian vision serves which parties. The article concludes that despite the efforts done by the private sector and the government to promote the New Administrative Capital as a model of smart cities in the Middle East, the project represents a neoliberal ideology inclined towards a business model than a social justice model and proposes a set of policies to restore the balance.